Relasi Semantik Hiponimik dan Sinonimik Bahasa Sasak Dialek Nggeto-Nggete - Lalu Fakihuddin; Muh. Jaelani Al Pansori; Lalu Mas'ud (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to describe the semantic relationships of hyponymy and synonymy in the Sasak language, specifically the nggeto-nggete dialect. The data sample was collected from Wanasaba Village, East Lombok, West Nusa Tenggara. This location was chosen for several reasons: it is one of the oldest villages on Lombok Island, it has a relatively large population, and the dialect variety is well understood by the researcher, who was born and raised there. These factors help minimize errors in understanding, analyzing, and describing the data. The data were collected through direct observation and personal experience. The analysis is based on a theoretical framework of hyponymy and synonymy drawn from selected linguistic experts. The findings indicate that the Sasak language in the nggeto-nggete dialect includes lexical items that demonstrate hyponymic and synonymic relationships. Hyponymic relations in the Sasak language involve not only classifiers and their subordinates but also relationships among the hyponyms themselves. Synonymic relations are found in nouns, verbs, and adjectives, where each class shares general semantic features while maintaining specific semantic distinctions that influence their contextual usage in sentences.